2019
DOI: 10.1101/731489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myristate can be used as a carbon and energy source for the asymbiotic growth of arbuscular mycorrhizal fungi

Abstract: 19Arbuscular mycorrhiza (AM) is one of the most widespread mutualistic symbioses, which is 20 formed between the majority of land plants and soil-borne fungi belonging to Glomeromycotina. 21 AM fungi are obligate symbionts that cannot complete their natural life cycle without a host. 22 Recent evidence suggests that lipids synthesized by a host are transferred to AM fungi that 23 possess no fatty acid synthase genes in their genome and that mutations in lipid biosynthesis-24 related genes of the host lea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Since some interesting work has recently highlighted pure cultures of AM fungi, especially those concerning the uptake of environmental lipids by fungal hyphae (Sugiura et al, 2019) and the promotive effects of ABA on sporulation (Liu et al, 2019), now is the right time to devote increased effort to strengthen these efforts. For instance, it is essential to clarify whether the enzymes hydrolyzing PLs in senescent arbuscules originate from plants or AM fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since some interesting work has recently highlighted pure cultures of AM fungi, especially those concerning the uptake of environmental lipids by fungal hyphae (Sugiura et al, 2019) and the promotive effects of ABA on sporulation (Liu et al, 2019), now is the right time to devote increased effort to strengthen these efforts. For instance, it is essential to clarify whether the enzymes hydrolyzing PLs in senescent arbuscules originate from plants or AM fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the transfer of lipids from plant cells to arbuscules is indispensable for AM symbiosis (Jiang et al, 2017). Recently, axenic culture of R. irregularis indicated that EH can take up lipids directly from the media and that myristate is the most effective fatty acid to promote hyphal growth, while (S)-12-methyltetradecanoic acid promotes both hyphal growth and sporulation (Kameoka et al, 2019;Sugiura et al, 2019).…”
mentioning
confidence: 99%
“…Recently, methyl-myristic acid (methyl-14:0) was shown to induce spore formation of R. irregularis [9]. Furthermore, myristic acid (14:0) supplementation to the medium was sufficient to support hyphal growth in axenic culture, 14:0 was taken up by the fungus and metabolized [10]. Taken together, these results suggest that a 14:0 or 16:0-containing lipid most likely is transferred from the host to the fungus where it serves as carbon source in addition to carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…These results mean that AM fungi require an external supply of lipids. Recently, Sugiura et al (2019), in a study published as a preprint on bioRxiv, provided evidence that AM fungi can complete their life cycle in the absence of a host when supplied with certain fatty acids, myristates (C:14, a common organic acid in plant root exudates; Li et al, 2017), in a variety of formulations (also see an earlier study on fatty acid effects on AM fungal growth by the same group; Kameoka et al, 2019). The significance of this finding for understanding the biology of these fungi and for their independent culture are immediately apparent.…”
mentioning
confidence: 99%
“…Before addressing these questions, it needs to be acknowledged that the study by Sugiura et al (2019) was a pioneering study. As such, it needs to still be independently verified as it was carried out with only one isolate, Rhizophagus irregularis, under controlled laboratory conditions.…”
mentioning
confidence: 99%